HARMONISASI FRASA RINGANNYA PERBUATAN DENGAN ASAS LEGALITAS TERKAIT IMPLEMENTASI RECHTERLIJK PARDON DI INDONESIA - Gandi, Fahrulian; Nashriana; Albariansyah, Hamonangan (UNIB Press, 2025)
The phrase “minor nature of the act” in the concept of rechterlijk pardon as regulated in Law No. 1 of 2023 has not yet been accompanied by interpretative guidelines. This situation may result in biased interpretations, leading to legal uncertainty and inconsistency in future law enforcement. This study examines the ideal regulation of the phrase “minor nature of the act” in rechterlijk pardon to ensure harmony with the principle of legality. The research employs normative legal methods, utilizing statutory, conceptual, case, and comparative approaches. The findings indicate that the phrase “minor nature of the act” should be limited to specific criminal offenses eligible for pardon, as exemplified in Portugal, in order to prevent multiple interpretations that could result in discrimination in law enforcement.